Resin composition

The inclusion of modified cellulose fibers and biomass-derived curing compounds in resin compositions addresses the mechanical strength issues of biomass-based resins, resulting in improved breakdown and stretching properties.

JP2025017180APending Publication Date: 2025-02-05KAO CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023120128
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-24
Publication Date
2025-02-05

AI Technical Summary

Technical Problem

Resin compositions derived from biomass often exhibit lower mechanical strength and hardness compared to conventional petroleum-based resins, necessitating improvements in mechanical properties.

Method used

A resin composition containing modified cellulose fibers with anionic groups, a biomass-derived thermal curing compound, and a curing agent, optionally with inorganic fillers, solvents, and dispersing agents, to enhance mechanical strength and hardness.

Benefits of technology

The modified cellulose fiber resin composition demonstrates improved breakdown and stretching properties, achieving enhanced mechanical strength and hardness in hardened objects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025017180000001
    Figure 2025017180000001
  • Figure 2025017180000002
    Figure 2025017180000002
  • Figure 2025017180000003
    Figure 2025017180000003
Patent Text Reader

Abstract

To provide a resin composition containing biomass-derived resin, which yields a cured product with improved elongation at break.SOLUTION: The present invention provides a resin composition containing a modified cellulose fiber, a biomass-derived thermosetting compound and a curing agent, and a coating, an adhesive or an insulating material containing the resin composition.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition. [Background technology]

[0002] Resin compositions, particularly epoxy resin compositions, are widely used in various fields such as coatings, construction, and electronics. Since many resin compositions are derived from petroleum, in light of the recent problem of global warming, various resin compositions utilizing biomass-derived materials have been proposed.

[0003] For example, Patent Document 1 discloses an epoxy resin composition that contains epoxidized linseed oil, which is a plant-derived material, a curing agent, a curing accelerator, and fused quartz.

[0004] However, the physical properties and functions of cured products and molded articles of biomass-derived resin compositions are often inferior to those of conventional petroleum-derived resins. For this reason, for example, Non-Patent Document 1 attempts to increase the mechanical strength by compounding epoxidized vegetable oil with a cellulose fiber sheet. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2016-166350 A [Non-patent literature]

[0006] [Non-Patent Document 1] Oleoscience, Vol. 14, pp. 117-122 (2014) Summary of the Invention [Problem to be solved by the invention]

[0007] On the other hand, in resin compositions containing biomass-derived resins, there is also a demand for improvement in the breaking elongation of the cured product. [Means for solving the problem]

[0008] The present invention relates to the following [1] to [6]. [1] A resin composition containing modified cellulose fibers, a biomass-derived thermosetting compound, and a curing agent. [2] The resin composition according to [1], wherein the modified cellulose fiber is a modified cellulose fiber obtained by bonding a modifying group to an anionic group of an anion-modified cellulose fiber. [3] The resin composition according to [1] or [2], further comprising one or more selected from the group consisting of inorganic fillers, solvents and dispersants. [4] A coating material containing the resin composition according to any one of [1] to [3] above. [5] An adhesive containing the resin composition according to any one of [1] to [3] above. [6] An insulating material containing the resin composition according to any one of [1] to [3] above. Effect of the Invention

[0009] The cured product obtained by molding the resin composition containing the biomass-derived resin of the present invention has the effect of being excellent in breaking elongation. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] As a result of the inventors' investigation into the composition of a cured product with excellent breaking elongation, they found that by blending modified cellulose fibers having a specific structure with a resin composition containing a biomass-derived thermosetting compound and a curing agent, the cured product of the obtained resin composition exhibits excellent breaking elongation, and thus completed the present invention. Although the mechanism by which the effects of the present invention are exerted is unclear, it is presumed that this is due to the fine dispersion of stress by the uniformly dispersed modified cellulose fibers.

[0011] <Resin composition> The resin composition of the present invention contains modified cellulose fibers, a biomass-derived thermosetting compound, and a curing agent.

[0012] [Modified cellulose fibers] The modified cellulose fiber in the present invention is preferably a modified cellulose fiber in which a modifying group is bonded to the anionic group of an anionically modified cellulose fiber.

[0013] (Anion-modified cellulose fiber) Anion-modified cellulose fibers are cellulose fibers having an anionic group, such as one or more groups selected from the group consisting of a carboxy group, a phosphate group, and a sulfonic acid group, in the molecule. The introduction of an anionic group into cellulose fibers can be achieved by the method described below. From the viewpoint of availability and effectiveness, anion-modified cellulose fibers having a carboxy group as the anionic group are preferred, and anion-modified cellulose fibers (referred to as "oxidized cellulose fibers") in which the group (-CH2OH) at the C6 position of the glucose unit constituting the cellulose fiber is selectively converted to a carboxy group are more preferred. The ion (counter ion) that is paired with the anionic group is preferably a proton.

[0014] The anionic group content in the anion-modified cellulose fiber is preferably 0.1 mmol / g or more, more preferably 0.4 mmol / g or more, and even more preferably 0.6 mmol / g or more, from the viewpoint of stable introduction of the modifying group. Also, from the viewpoint of improving the handleability, it is preferably 3 mmol / g or less, more preferably 2 mmol / g or less, even more preferably 1.8 mmol / g or less, and even more preferably 1.5 mmol / g or less. The "anionic group content" means the total amount of anionic groups in the glucose constituting the cellulose fiber, and is specifically measured by the method described in the Examples below.

[0015] The preferred ranges of the average fiber diameter and average fiber length of the anionically modified cellulose fibers are similar to those of the raw material cellulose fibers, although they depend on the order of the production steps.

[0016] The modification group is bonded to the anionic group of the anion-modified cellulose fiber, which means that the modification group is bonded to the anionic group, preferably the carboxy group, of the anion-modified cellulose fiber. The bond between the modification group and the anionic group can be an ionic bond and / or a covalent bond. Examples of the covalent bond include an amide bond, an ester bond, and a urethane bond, and an amide bond is preferred.

[0017] (modifying group) The modifying group may be a hydrocarbon group, an alkylene oxide chain, or a silicone group. One or more of these modifying groups may be bonded (introduced) to the anion-modified cellulose fiber. In the present invention, the modifying group is preferably an alkylene oxide chain, from the viewpoint of obtaining a cured product of the resin composition excellent in breaking elongation.

[0018] (1) Hydrocarbon group Examples of the hydrocarbon group include a chain saturated hydrocarbon group, a chain unsaturated hydrocarbon group, a cyclic saturated hydrocarbon group, and an aromatic hydrocarbon group. Specific examples of such hydrocarbon groups include those described in paragraphs 0020 to 0025 of JP2022-001634A.

[0019] (2) Alkylene oxide chain The alkylene oxide chain is a structure containing a (co)polymer of ethylene oxide (EO) or propylene oxide (PO), and is preferably one or more (co)polymer moieties selected from the group consisting of a structure containing a polymer of EO (EO polymerization moiety), a structure containing a polymer of PO (PO polymerization moiety), and a structure containing a copolymer in which EO and PO are polymerized randomly or in a block form (EO / PO copolymer moiety). The alkylene oxide chain may further have a substituent described later. In the present invention, the modifying group is more preferably an EO / PO copolymer moiety, from the viewpoint of obtaining a cured resin composition excellent in elongation at break.

[0020] Examples of the EO polymerization portion, the PO polymerization portion, or the EO / PO copolymerization portion include those described in paragraphs 0028 to 0035 of JP2022-001634A.

[0021] (3) Silicone group The silicone group is a monovalent group having a siloxane bond as the main chain, and may be accompanied by an alkylene group.

[0022] (4) Further Substituents The modifying group may further have a substituent. Examples of the substituent include those described in paragraph 0036 of JP2022-001634A.

[0023] [Method for producing modified cellulose fibers] The modified cellulose fiber can be produced by a known production method, for example, by introducing an anionic group into a raw cellulose fiber to produce an anion-modified cellulose fiber, and then bonding a modifying group to the anionic group of the anion-modified cellulose fiber. More specifically, the methods described in paragraphs 0037 to 0076 of JP 2022-001634 A can be mentioned.

[0024] (Refining process) By micronizing the cellulose fibers at any stage of the manufacturing method of the modified cellulose fibers, the cellulose fibers of the micrometer scale can be micronized to the nanometer scale. By reducing the average fiber diameter to the nanometer size, the dispersibility in the resin is improved, which is preferable.

[0025] The micronization treatment can be carried out by a known micronization treatment method. For example, when obtaining modified cellulose fibers having an average fiber diameter of nanometer size, a treatment method using a grinder such as a mass colloider or a treatment method using a high-pressure homogenizer in a medium may be carried out. Specific examples of media and devices used in the micropatterning process are described in paragraphs 0079 to 0080 of JP 2022-001634 A.

[0026] (Short fiber processing) At any stage of the production method of the modified cellulose fiber, the cellulose fiber may be further subjected to a fiber shortening treatment, i.e., a treatment for shortening the fiber length. The fiber shortening treatment may be achieved by subjecting the cellulose fiber to a known treatment, such as one or more treatment methods selected from the group consisting of alkali treatment, acid treatment, heat treatment, ultraviolet treatment, electron beam treatment, mechanical treatment, and enzyme treatment.

[0027] [Properties of modified cellulose fibers] The main properties of the modified cellulose fiber of the present invention are as follows:

[0028] (Average fiber diameter) The average fiber diameter of the modified cellulose fiber is preferably 5 μm or more, regardless of the type of modifying group. From the viewpoints of handling, availability, and cost, it is more preferably 7 μm or more, even more preferably 10 μm or more, and even more preferably 15 μm or more. In addition, although there is no particular upper limit, from the viewpoint of handling, it is preferably 10,000 μm or less, more preferably 5,000 μm or less, even more preferably 1,000 μm or less, even more preferably 500 μm or less, and even more preferably 100 μm or less. The average fiber diameter of the modified cellulose fiber is determined by the method described in the Examples below.

[0029] The modified cellulose fiber may be one that has been subjected to a micronization treatment to have a nanometer size. In this case, the average fiber diameter of the modified cellulose fiber is preferably 1 nm or more, more preferably 2 nm or more, from the viewpoints of handling, availability, and cost, and is preferably 500 nm or less, more preferably 300 nm or less, even more preferably 200 nm or less, even more preferably 150 nm or less, and even more preferably 120 nm or less, from the viewpoints of handling and solvent dispersibility. The average fiber diameter of the modified cellulose fiber that has been subjected to a micronization treatment is determined by the method described in the Examples below.

[0030] (Modification group binding amount and introduction rate) The amount of the modifying group bonded to the modified cellulose fiber is preferably 0.01 mmol / g or more from the viewpoint of dispersibility, and from the same viewpoint, is preferably 3.0 mmol / g or less. When any two or more kinds of modifying groups are simultaneously introduced into the modified cellulose fiber as the modifying groups, the amount of the modifying groups bonded is preferably within the above range.

[0031] From the viewpoint of dispersibility, the introduction rate of the modifying group in the modified cellulose fiber is preferably 10 mol% or more, the higher the better, and is preferably 100 mol%. When any two or more types of modifying groups are simultaneously introduced as the modifying group, it is preferable that the introduction rate is within the above range as long as the total introduction rate does not exceed the upper limit of 100 mol%.

[0032] The bonded amount and introduction rate of the modifying group can be adjusted by the type and amount of the modifying compound added, reaction temperature, reaction time, type of solvent, etc. The bonded amount (mmol / g) and introduction rate (mol%) of the modifying group refer to the amount and ratio of the modifying group introduced (bonded) to the anionic group in the modified cellulose fiber. For example, when the anionic group is a carboxy group, the bonded amount and introduction rate of the modifying group in the modified cellulose fiber are calculated by the method described in the Examples below.

[0033] (Crystal structure) The modified cellulose fiber preferably has a cellulose I type crystal structure, and the crystallinity of the modified cellulose fiber is preferably 10% or more, more preferably 15% or more, and even more preferably 20% or more from the viewpoint of the breaking elongation of the cured product of the resin composition. In addition, from the viewpoint of raw material availability, it is preferably 90% or less, more preferably 85% or less, even more preferably 80% or less, and even more preferably 75% or less. In this specification, the crystallinity of the cellulose fiber is the cellulose I type crystallinity calculated from the diffraction intensity value by the X-ray diffraction method, and can be measured according to the method described in the examples below. In addition, the cellulose I type refers to the crystalline form of natural cellulose fiber, and the cellulose I type crystallinity refers to the proportion of the amount of crystalline region in the entire cellulose fiber. The presence or absence of the cellulose I type crystal structure can be determined by the presence of a peak at 2θ=22.6° in X-ray diffraction measurement.

[0034] [Biomass-derived thermosetting compound] In the present invention, the biomass-derived thermosetting compound is preferably an epoxidized product of biomass or a compound of a sugar and a glycidyl ether.

[0035] Examples of biomass include vegetable oils (linseed oil, hemp oil, sunflower oil, rapeseed oil, soybean oil, olive oil, grapeseed oil, tung oil, cottonseed oil, corn oil, hazelnut oil, walnut oil, coconut oil, palm oil, castor oil, cashew nut oil, peanut oil, gourd oil, neem oil, loofah oil, olive kernel oil, sesame oil, almond oil, poppy seed oil, terpenes, apricot kernel oil, beechnut oil), animal oils (lard, beef tallow, fish oil, whale oil), etc.

[0036] Biomass can also include substances other than fats and oils, such as natural rubber, polyhydric alcohols (e.g., (poly)glycerol, cardanol, furans, etc.), lignin, lignophenol, tannin, kraft lignin, etc. Such biomass can be obtained from wood and its chips, various grasses, rice straw, etc.

[0037] An epoxidized biomass can be prepared by adding an epoxy group to biomass. Methods for synthesizing an epoxidized biomass are known, and for example, lignin or lignophenol can be epoxidized by the method described in JP 2010-150298 A.

[0038] Epoxidized biomass is commercially available as a plasticizer, and commercially available products can be used in the present invention. Specific examples of commercially available products include epoxidized soybean oil, epoxidized linseed oil, epoxidized sunflower oil, epoxidized rapeseed oil, epoxidized peanut oil, epoxidized olive kernel oil, epoxidized castor oil, epoxidized sesame oil, epoxidized almond oil, and epoxidized poppy oil.

[0039] Examples of compounds of sugars and glycidyl ethers include isosorbide diglycidyl ether, sorbitol polyglycidyl ether, glycerol polyglycidyl ether, and polyglycerol polyglycidyl ether.

[0040] The resin composition of the present invention may contain a thermosetting compound other than the biomass-derived thermosetting compound (for example, a petroleum-derived epoxy resin).

[0041] [Curing agent and curing accelerator] The resin composition of the present invention contains a curing agent and may further contain a curing accelerator as required.

[0042] The curing agent can be appropriately selected according to the type and application of the biomass-derived thermosetting compound. For example, when the biomass-derived thermosetting compound is an epoxidized product of biomass, examples of the curing agent include amine-based curing agents, phenolic resin-based curing agents, acid anhydride-based curing agents, imidazole-based curing agents, polymercaptan-based curing agents, and latent curing agents (boron trifluoride-amine complex, dicyandiamide, carboxylic acid hydrazide, etc.). The curing agent may be used alone or in combination of two or more kinds. In addition, the curing agent may act as a curing accelerator.

[0043] Examples of the curing agent that can be preferably used in the present invention include amines (e.g., 4,4'-diaminodiphenylsulfone, diaminodiphenylmethane), and acid anhydrides (e.g., anhydrides of fumaric acid, maleic acid, succinic acid, dodecenylsuccinic acid, tetrahydrophthalic acid, methyltetrahydrophthalic acid, hexahydrophthalic acid, methylhexahydrophthalic acid, itaconic acid, citraconic acid, etc.), and more preferably, methylhexahydrophthalic anhydride (MHHPA).

[0044] The ratio of the curing agent can be appropriately selected depending on the type of the curing agent, and is preferably 0.05 to 300 parts by mass, for example, with respect to 100 parts by mass of the biomass-derived thermosetting compound. In particular, when an amine-based curing agent is used, the active hydrogen equivalent is preferably 0.85 times or more, more preferably 0.9 times or more, and on the other hand, preferably 1.15 times or less, more preferably 1.1 times or less, with respect to the number of moles of epoxy in the epoxidized product, and is particularly preferably 1.0 times with respect to the number of moles of epoxy in the epoxidized product. In addition, when an acid anhydride-based curing agent is used, the acid anhydride equivalent is preferably 0.85 times or more, more preferably 0.9 times or more, and on the other hand, preferably 1.15 times or less, more preferably 1.1 times or less, with respect to the number of moles of epoxy in the epoxidized product, and is particularly preferably 1.0 times with respect to the number of moles of epoxy in the epoxidized product.

[0045] The curing accelerator can also be appropriately selected depending on the type of biomass-derived thermosetting compound, the type of curing agent, and the application, and examples of the curing accelerator when the biomass-derived thermosetting compound is an epoxidized product of biomass include phosphines, amines, imidazoles, N,N-dialkylureas, etc. The curing accelerators may be used alone or in combination of two or more.

[0046] When an acid anhydride is used as the curing agent, examples of the curing accelerator that can be preferably used in the present invention include tertiary amines, tertiary amine salts, imidazoles (e.g., 2-methylimidazole, 2-ethylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, etc.), N,N-dialkyl ureas such as N,N-dimethyl-N'-(3,4-dichlorophenyl)urea, dialkyl urea compounds such as N,N'-dialkyl urea compounds; N,N'-dialkylthiourea compounds, organic phosphorus compounds, quaternary ammonium salts, quaternary phosphonium salts, organic metal salts, and boron compounds.

[0047] The ratio of the curing accelerator can be appropriately selected depending on the type of curing agent, and is preferably 0.01 to 100 parts by mass, for example, relative to 100 parts by mass of the biomass-derived thermosetting compound.

[0048] [Inorganic filler] The composition of the present invention may further contain an inorganic filler. By containing an inorganic filler, the effects of increasing the amount of the composition, adjusting the viscosity or reducing the weight, and reinforcing the cured product can be expected. In addition, the effects of improving the heat resistance, thermal conductivity, electrical conductivity, insulation, and ultraviolet shielding properties of the cured product can be expected. Specific examples of inorganic fillers include calcium carbonate, talc, titanium oxide, mica, silica, alumina, hollow glass beads, calcium oxide, boron nitride, aluminum nitride, silicon nitride, gallium nitride, magnesium oxide, zinc oxide, aluminum oxide, silicon carbide, silicon dioxide, carbon black, clay, kaolin, zeolite, zirconia, glass fiber, and carbon fiber. Only one type of inorganic filler may be used, or two or more types may be used.

[0049] The shape of the inorganic filler is not particularly limited, and it may be in the form of particles or fibers. When the inorganic filler is particulate, the average particle size is preferably 0.1 μm or more, more preferably 0.5 μm or more, from the viewpoints of workability of the composition and reinforcement of the cured product, and from the same viewpoints, is preferably 100 μm or less, more preferably 50 μm or less. The average particle size of the inorganic filler is determined by measuring the particle sizes (average of major and minor axes) of 500 particles from a scanning electron microscope (SEM) photograph, and taking the number average value of these.

[0050] [Solvent or Dispersion Medium] The resin composition may contain a solvent or a dispersion medium within a range that does not impair the effects of the present invention. Examples of such a solvent or dispersion medium in the present invention include organic solvents and organic media containing reactive functional groups, and are not particularly limited as long as they are used in the field of coating materials.

[0051] From the viewpoint of obtaining a smooth film when the resin composition is applied, the solvent etc. used in the present invention preferably has a dielectric constant at 25° C. of 75 or less, more preferably 55 or less, even more preferably 45 or less, preferably 1 or more, more preferably 2 or more, and even more preferably 3 or more. The dielectric constant of the solvent can be measured at 25° C. using a liquid dielectric meter Model 871 (manufactured by Nippon Luft Co., Ltd.).

[0052] Examples of organic solvents include alcohols such as methanol, ethanol, isopropyl alcohol, 2-butanol, 1-pentanol, octyl alcohol, glycerin, ethylene glycol, and propylene glycol; carboxylic acids such as acetic acid; hydrocarbons such as hexane, heptane, octane, decane, and liquid paraffin; aromatic hydrocarbons such as toluene and xylene; amides such as dimethyl sulfoxide, N,N-dimethylformamide, dimethylacetamide, and acetanilide; ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; halogens such as methylene chloride and chloroform; and ethylene Examples of the oil-soluble organic solvent include carbonates such as propylene carbonate, dimethyl carbonate, and diethyl carbonate; esters such as methyl acetate, ethyl acetate, propyl acetate, butyl acetate, methyl butyrate, sorbitan fatty acid esters, polyoxyethylene sorbitan fatty acid esters, polyoxyethylene sorbitol fatty acid esters, glycerin fatty acid esters, and polyoxyethylene fatty acid esters; polyethers such as polyethylene glycol and polyoxyethylene alkyl ether; silicone oils such as polydimethylsiloxane; acetonitrile, propionitrile, ester oils, salad oils, soybean oil, and castor oil. These oils may be used alone or in combination of two or more.

[0053] Examples of organic media containing reactive functional groups include acrylates such as methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, butyl acrylate, butyl methacrylate, n-hexyl acrylate, n-hexyl methacrylate, 2-ethylhexyl acrylate, 2-ethylhexyl methacrylate, and phenyl glycidyl ether acrylate; urethane prepolymers such as hexamethylene diisocyanate urethane prepolymer and phenyl glycidyl ether acrylate toluene diisocyanate urethane prepolymer; glycidyl ethers such as n-butyl glycidyl ether, 2-ethylhexyl glycidyl ether, glycidyl ether of stearic acid, styrene oxide, phenyl glycidyl ether, nonylphenyl glycidyl ether, butylphenyl glycidyl ether, 1,6-hexanediol diglycidyl ether, ethylene glycol diglycidyl ether, and diethylene glycol diglycidyl ether; chlorostyrene, methoxystyrene, butoxystyrene, and vinyl benzoic acid.

[0054] When a solvent or dispersion medium is used, the content of the solvent or dispersion medium in the composition of the present invention is preferably 30% by mass or more, more preferably 50% by mass or more, and even more preferably 80% by mass or more, from the viewpoint of obtaining a smooth film when the resin composition is applied. On the other hand, from the same viewpoint, it is preferably 98% by mass or less, more preferably 97% by mass or less, and even more preferably 96% by mass or less. If necessary, the solvent or dispersion medium may be partially or entirely removed from the composition of the present invention. Therefore, the composition of the present invention may be in the form of a solution or dispersion, or may be in the form of a dried powder.

[0055] [Other ingredients] The resin composition may contain, for example, plasticizers, crystal nucleating agents, fillers (inorganic fillers, organic fillers), hydrolysis inhibitors, flame retardants, antioxidants, lubricants such as hydrocarbon waxes and anionic surfactants, ultraviolet absorbers, antistatic agents, antifogging agents, light stabilizers, pigments, antifungal agents, antibacterial agents, foaming agents, surfactants; polysaccharides such as starches and alginic acid; natural proteins such as gelatin, glue, and casein; inorganic compounds such as tannins, ceramics, and metal powders; fragrances; flow regulators; leveling agents; conductive agents; ultraviolet dispersion agents; deodorants; and other inorganic fibers, within the scope of the present invention. Furthermore, it is also possible to add other polymer materials and other compositions within the scope of the present invention.

[0056] [Composition of Resin Composition] The amount of modified cellulose fiber in the composition of the present invention is preferably 0.2% by mass or more, more preferably 0.5% by mass or more, and even more preferably 1% by mass or more, in terms of cellulose fiber (not including modification groups) in terms of blending amount, from the viewpoint of obtaining a cured product of the resin composition excellent in breaking elongation, while it is preferably 50% by mass or less, more preferably 40% by mass or less, even more preferably 30% by mass or less, and even more preferably 10% by mass or less. The amount of modified cellulose fiber in the composition of the present invention is preferably 0.2% by volume or more, more preferably 0.4% by volume or more, and even more preferably 0.8% by volume or more, while it is preferably 50% by volume or less, more preferably 40% by volume or less, even more preferably 30% by volume or less, and even more preferably 10% by volume or less. The volume percentage of each component in the resin composition is determined from the volume ratio of each component when blended.

[0057] The content of the biomass-derived thermosetting compound in the composition of the present invention, calculated in terms of the blending amount, is preferably 30% by mass or more, more preferably 40% by mass or more, even more preferably 50% by mass or more, and is preferably 99.5% by mass or less, more preferably 99% by mass or less, even more preferably 98% by mass or less, and even more preferably 97% by mass or less. The amount of the biomass-derived thermosetting compound in the composition of the present invention is preferably 10% by volume or more, more preferably 20% by volume or more, and even more preferably 30% by volume or more, and is preferably 99.5% by volume or less, more preferably 99% by volume or less, even more preferably 98% by volume or less, and even more preferably 97% by volume or less.

[0058] When an inorganic filler is contained, the content of the inorganic filler in the composition of the present invention is preferably 10 vol% or more, more preferably 20 vol% or more, while it is preferably 90 vol% or less, more preferably 80 vol% or less.

[0059] Therefore, one preferred embodiment of the resin composition of the present invention is a resin composition containing modified cellulose fiber, a biomass-derived thermosetting compound, and a curing agent, and further containing one or more selected from the group consisting of inorganic fillers, solvents, and dispersants.

[0060] [Method for producing resin composition] The resin composition of the present invention can be produced, for example, by mixing the modified cellulose fiber, the biomass-derived thermosetting compound, the curing agent, and, if necessary, a solvent and the like. For example, the above-mentioned components can be melt-kneaded using a known kneader such as an internal kneader, a single-screw or twin-screw extruder, a roll mill, or an open-roll type kneader, or can be sheared by a solvent casting method or by a shearing device such as a high-shear processing machine.

[0061] The amount of modified cellulose fiber to be mixed is preferably 0.06 parts by mass or more, more preferably 0.12 parts by mass or more, even more preferably 0.36 parts by mass or more, even more preferably 0.6 parts by mass or more, and even more preferably 1 part by mass or more, relative to 100 parts by mass of the biomass-derived thermosetting compound, from the viewpoint of obtaining a cured product excellent in breaking elongation. On the other hand, from the viewpoint of production cost, it is preferably 120 parts by mass or less, more preferably 100 parts by mass or less, even more preferably 60 parts by mass or less, even more preferably 40 parts by mass or less, and even more preferably 20 parts by mass or less.

[0062] [Uses of resin composition] The resin composition of the present invention can be used in various industrial fields. An example of the application of the resin composition is a coating material containing the resin composition of the present invention. By coating a substrate surface with a cured coating film of the resin composition of the present invention, it is expected that the substrate can be protected for a long period of time from collision objects such as raindrops and dust, ultraviolet rays, etc. Further, an example of the use of the resin composition is an adhesive containing the resin composition of the present invention. By applying the resin composition of the present invention to an adhesive, the effect of excellent adhesive performance can be expected. Further, an example of the use of the resin composition includes an insulating material containing the resin composition of the present invention. The resin composition of the present invention is expected to form a cured layer that serves as an insulating layer having a good balance between mechanical strength and adhesion to a substrate. Further, an example of the use of the resin composition includes a structural material containing the resin composition of the present invention. By applying the resin composition of the present invention to a structural material, it is expected that the cured molded product will have excellent mechanical strength.

[0063] The cured product of the resin composition of the present invention can be molded to produce a resin molded product. The resin molded product can be produced by appropriately using a known molding method such as coating molding, extrusion molding, injection molding, press molding, cast molding, or solvent casting of the composition of the present invention. Among these known molding methods, coating molding and cast molding are preferred from the viewpoint of productivity. EXAMPLES

[0064] The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to the following examples. Parts in the examples are parts by weight unless otherwise specified. "Normal pressure" refers to 101.3 kPa, and "normal temperature" refers to 25°C.

[0065] [Average fiber diameter of various cellulose fibers] (1) When the average fiber diameter of the cellulose fibers to be measured is expected to be several nanometers to several hundred nanometers, the average fiber diameter of the cellulose fibers is determined as follows. A suitable solvent is added to the cellulose fiber or cellulose fiber dispersion to be measured to prepare a dispersion with a content of 0.0001% by mass, and the dispersion is dropped onto mica and dried to be used as an observation sample. The fiber height (difference in height between where the fiber is present and where it is not present) of the cellulose fiber in the observation sample is measured using an atomic force microscope (AFM) (Nanoscope III Tapping mode AFM manufactured by Digital Instrument, Inc., probe is Point Probe (NCH) manufactured by Nanosensors, Inc.). The suitable solvent is any solvent that swells the cellulose fiber to be measured, and in the case of cellulose fiber, water or ethanol is preferable, and in the case of modified cellulose fiber or finely modified cellulose fiber, DMF, MEK, toluene, etc. are preferable. At that time, in a microscope image in which the cellulose fiber can be confirmed, 100 or more cellulose fibers are extracted, and the average fiber diameter is calculated from the fiber height. The average fiber length is calculated from the distance in the fiber direction. The average aspect ratio is calculated from the average fiber length / average fiber diameter, and the standard deviation is also calculated. Generally, the smallest unit of cellulose nanofibers prepared from higher plants is a 6 × 6 molecular chain packed in an approximately square shape, so the height analyzed in an AFM image can be regarded as the width of the fiber.

[0066] (2) When the average fiber diameter of the cellulose fibers to be measured is expected to be several hundred nanometers to several thousand micrometers, the average fiber diameter of the cellulose fibers is determined as follows. A medium is added to the cellulose fibers to be measured to prepare a dispersion liquid with a content of 0.01% by mass. The dispersion liquid is measured using a wet dispersion type image analysis particle size distribution meter (manufactured by Jusco International, product name: IF-3200) under the following conditions: front lens: 2x, telecentric zoom lens: 1x, image resolution: 0.835 μm / pixel, syringe inner diameter: 6515 μm, spacer thickness: 500 μm, image recognition mode: ghost, threshold: 8, analysis sample amount: 1 mL, sampling: 15%. 100 or more cellulose fibers are measured, and the average ISO fiber diameter and average ISO fiber length are calculated as the average fiber diameter and average fiber length, respectively. The average aspect ratio is calculated from the average fiber length / average fiber diameter, and the standard deviation is also calculated.

[0067] [Anionic group content of various cellulose fibers] A 100 mL beaker is filled with 0.5 g of cellulose fiber to be measured, and ion-exchanged water or a 2 / 1 mixed solvent of methanol and water is added to make a total of 55 mL. 5 mL of 0.01 M aqueous sodium chloride solution is added to the beaker to prepare a dispersion. The dispersion is stirred until the cellulose fiber to be measured is sufficiently dispersed. 0.1 M hydrochloric acid is added to the dispersion to adjust the pH to 2.5 to 3, and an automatic titration device (manufactured by DKK-TOA Corporation, product name "AUT-701") is used to drop 0.05 M aqueous sodium hydroxide solution into the dispersion with a waiting time of 60 seconds, and the conductivity and pH value are measured every minute. The measurement is continued until the pH reaches about 11, and a conductivity curve is obtained. The sodium hydroxide titration amount is determined from the conductivity curve, and the anionic group content of the cellulose fiber to be measured is calculated using the following formula.

[0068] Anionic group content (mmol / g) = sodium hydroxide titration amount × sodium hydroxide aqueous solution concentration (0.05M) / mass of cellulose fiber to be measured (0.5g)

[0069] [Confirmation of the crystal structure of cellulose fibers] The crystal structures of various cellulose fibers, such as raw cellulose fiber, anion-modified cellulose fiber, and modified cellulose fiber, are confirmed by measurement under the following conditions using a diffractometer (manufactured by Rigaku Corporation, trade name: MiniFlexII). Measurement pellet preparation conditions: A pressure of 10 to 20 MPa was applied to the target cellulose fiber using a tablet forming machine to produce pellets with an area of ​​320 mm 2 Prepare a smooth pellet with a thickness of ×1 mm. X-ray diffraction analysis conditions: step angle 0.01°, scan speed 10° / min, measurement range: diffraction angle 2θ=5~40° X-ray source: Cu / Kα-radiation, tube voltage: 15kv, tube current: 30mA Peak splitting conditions: After removing background noise, perform fitting with a Gaussian function so that the error between 2θ=13-23° is within 5%.

[0070] The crystal structures of various cellulose fibers are confirmed by measuring them using the above-mentioned diffractometer under the above-mentioned conditions. The degree of crystallinity of the cellulose type I crystal structure is calculated based on the following formula (A) using the area of ​​the X-ray diffraction peak obtained by the above-mentioned peak division. Cellulose type I crystallinity (%) = [I cr / (I cr +I am )]×100 (A) [In the formula, I cr is the area of ​​the diffraction peak of the lattice plane (002 plane) (diffraction angle 2θ = 22-23°) in X-ray diffraction, I am indicates the area of ​​the diffraction peak of the amorphous part (diffraction angle 2θ = 18.5°).

[0071] [Amount of modified group bonded and introduction rate in modified cellulose fiber] The amount of modified groups bonded is determined by the following IR measurement method, and the amount of bonded and the introduction rate are calculated by the following formula: Specifically, the IR measurement is performed by measuring the dried anion-modified cellulose fiber or modified cellulose fiber by the ATR method using an infrared absorption spectrometer (IR) (manufactured by Thermo Fisher Scientific, product name: Nicolet 6700), and the amount of modified groups bonded and the introduction rate are calculated by the following formulas A and B. <Formula A> Amount of modified group bound (mmol / g) = a × (bc) ÷ d a: Carboxylic group content of oxidized cellulose fiber (mmol / g) b: 1720 cm of oxidized cellulose fiber -1 Peak intensity of c: 1720 cm of modified cellulose fiber -1 Peak intensity of d: 1720 cm of oxidized cellulose fiber -1 Peak intensity of 1720cm -1 Peak intensity: Peak intensity derived from the carbonyl group of carboxylic acid <Formula B> Modification group introduction rate (mol%) = 100 × e / f e: Amount of modified group bound (mmol / g) f: Carboxylic group content of oxidized cellulose fiber (mmol / g)

[0072] [Amount of cellulose fiber in modified cellulose fiber (equivalent amount)] The amount of cellulose fiber (equivalent amount) in the modified cellulose fiber is the amount of cellulose fiber in the modified cellulose fiber excluding the modifying group. In the modified cellulose fiber of the present invention, the formula weight of the modifying group may be considerably larger (for example, larger than the molecular weight of glucose), so in this specification, when it is appropriate to explain the modified cellulose fiber without considering the difference in the formula weight of the modifying group, the amount of cellulose fiber constituting the modified cellulose fiber (equivalent amount) is expressed instead of the amount of modified cellulose fiber.

[0073] The amount of cellulose fiber (converted amount) is measured by the following method. (a) When one type of "modifying compound" is added The amount of cellulose fiber (equivalent amount) is calculated by the following formula E. <Formula E>: Amount of cellulose fiber (converted amount) (g) = mass of modified cellulose fiber (g) / [1 + molecular weight of modifying compound (g / mol) × bond amount of modifying group (mmol / g) × 0.001] (b) When two or more types of "modifying compounds" are added The amount of cellulose fiber (converted amount) is calculated taking into consideration the molar ratio of each compound (that is, the molar ratio when the total molar amount of the modifying compounds to be added is taken as 1).

[0074] [Production of anionically modified cellulose fibers] Manufacturing Example 1 Bleached coniferous kraft pulp (West Fraser, product name: Hinton) was used as the natural cellulose fiber. A commercially available TEMPO product (ALDRICH, free radical, 98% by mass) was used. A commercially available sodium hypochlorite product (Wako Pure Chemical Industries, 10.5% by mass aqueous solution) was used. A commercially available sodium bromide product (Wako Pure Chemical Industries, Ltd.) was used.

[0075] First, 10 g of the bleached kraft pulp was thoroughly stirred with 990 g of ion-exchanged water, and then 0.13 g of TEMPO, 1.3 g of sodium bromide, and 27 g of 10.5 mass% sodium hypochlorite aqueous solution were added in this order to the 10 g of pulp. Using pH stat titration with an automatic titration device (manufactured by DKK-TOA Corporation, product name: AUT-701), 0.5 M sodium hydroxide aqueous solution was added dropwise to maintain the pH at 10.5. After the reaction was carried out for 120 minutes (20°C) at a stirring speed of 200 rpm, the addition of sodium hydroxide was stopped, and an anion-modified cellulose fiber in which the anionic group was a carboxyl group was obtained.

[0076] The anion-modified cellulose fiber was neutralized with 0.01 M hydrochloric acid, and then thoroughly washed with ion-exchanged water until the electrical conductivity of the filtrate measured with a compact electrical conductivity meter (HORIBA, Ltd., LAQUAtwin EC-33B) was 200 μs / cm or less, and then dehydrated. The carboxyl group content of the anion-modified cellulose fiber was 1.3 mmol / g.

[0077] The suspension of the anion-modified cellulose fiber having a solid content of 144.5 g is diluted with 1000 g of deionized water, to which 1.4 g of 35% hydrogen peroxide solution (1 part by mass of hydrogen peroxide per 100 parts by mass of the solid content of the raw cellulose fiber) is added, and the pH is adjusted to 12 with 1 M aqueous sodium hydroxide solution. Then, an alkaline hydrolysis treatment is performed at 80° C. for 2 hours (solid content of the suspension of the anion-modified cellulose fiber is 4.3% by mass). After the suspension is cooled to room temperature, the solid content is filtered off by suction filtration. The operation of dispersing the solid content in deionized water and filtering the solid content by suction filtration is repeated until the conductivity of the filtrate is 200 μs / cm or less. Deionized water is added to the suspension so that the solid content concentration in the suspension is 5% by mass, and the mixture is stirred at 95° C. for 12 hours, and then cooled to room temperature to obtain an aqueous suspension of shortened anion-modified cellulose fiber.

[0078] 100 g of the resulting aqueous suspension of short fiber anion-modified cellulose fibers (solid content concentration 5% by mass) was subjected to solid-liquid separation by centrifugation to obtain a residue. 250 g of PGME was added to the resulting residue, and 3.4 g of EOPO amine (HUNTSMAN, Jeffamine M2070; Mw = 2000, EO:PO = 31:10) was added, and the mixture was stirred at 25 ° C for 1 hour. The resulting mixture was subjected to dispersion treatment at 150 MPa for 5 passes using a high-pressure homogenizer (Yoshida Machine, Nanovater L-ES). Next, the resulting mixture was subjected to pressure filtration using a 6 μm mesh to obtain a PGME dispersion of modified cellulose fibers.

[0079] [Production of resin composition] Example A1 The dispersion finally obtained in Production Example 1 was added to 5 g of epoxidized soybean oil (ADEKA Adeka Cizer O-130P) so that the solid content was 0.1 g in terms of the amount of short fiber anion-modified cellulose fiber, and the mixture was stirred at 25°C for an additional hour. The solvent was removed from the resulting dispersion using an evaporator to obtain a resin composition containing modified cellulose fiber and epoxidized soybean oil. The resulting modified cellulose fiber had a bond amount of modifying groups of 0.34 mmol / g, a modification group introduction rate of 26 mol%, and a cellulose I type crystallinity of 65%.

[0080] Example A2 A resin composition containing modified cellulose fiber and epoxidized linseed oil was produced in the same manner as in Example A1, except that epoxidized linseed oil (ADEKA Adeka Cizer O-180A) was used instead of epoxidized soybean oil (ADEKA Adeka Cizer O-130P).

[0081] [Production of cured resin composition] Example B1 The resin composition obtained in Example A1 (59.2% by mass) was mixed with 40.2% by mass of methylhexahydrophthalic anhydride (MHHPA) as a curing agent and 0.6% by mass of 2-ethyl-4-methyl-imidazole as a curing accelerator, and was stirred at 2000 rpm for 5 minutes and degassed at 2200 rpm for 2 minutes at room temperature using an automatic revolution type mixer (Thinky Corporation, Awatori Rentaro). The mixture obtained was applied to a copper foil with a coating thickness of 250 μm using an applicator (Tester Sangyo Co., Ltd.). After that, the mixture was heated in a dryer at 130 ° C for 1 hour, and then further heated at 150 ° C for 1 hour to heat cure, producing a cured product of the resin composition.

[0082] Example B2 A cured resin composition was produced in the same manner as in Example B1, except that the resin composition was 53.3 mass% of the resin composition obtained in Example A2, the curing agent was 46.2 mass% of methylhexahydrophthalic anhydride (MHHPA), and the curing accelerator was 0.5 mass% of 2-ethyl-4-methyl-imidazole.

[0083] Comparative Example 1 A cured resin composition was produced in the same manner as in Example B1, except that the resin composition was 58.4 mass% epoxidized soybean oil (ADEKA Cizer O-130P), 41.0 mass% MHHPA, and 0.6 mass% 2-ethyl-4-methyl-imidazole as a curing accelerator.

[0084] Comparative Example 2 A cured resin composition was produced in the same manner as in Example B1, except that the resin composition was 52.5 mass% epoxidized linseed oil (ADEKA Adeka Cizer O-180A), 47.0 mass% MHHPA, and 0.5 mass% 2-ethyl-4-methyl-imidazole.

[0085] [Measurement of breaking elongation] Test Example 1 Each cured product was punched out into a rectangular shape of 5×40 mm, and a tensile test was performed on the cured product to measure the breaking elongation (%), which is the elongation at break. The measurement was performed using a bench-top precision universal testing machine (Shimadzu Corporation, AGS-X) with a load cell of 1000 N, a chuck distance of 20 mm, and a tensile speed of 1 mm / min at 25°C. The average thickness of three points was used for the test piece. The breaking elongation was measured five times under the above conditions, and the average value is shown in Table A as the breaking elongation. The larger the breaking elongation (%), the better the mechanical strength of the cured product.

[0086] [Table A]

[0087] From Table A, it can be seen that the examples incorporating modified cellulose fibers have higher breaking elongation values ​​than the corresponding comparative examples.

[0088] Prescription Examples Formulation examples of the resin composition of the present invention are disclosed below. Details of the main ingredients used in the formulation examples are as follows. Note that some ingredients available as reagents have been omitted.

[0089] (1) Modified cellulose fibers The modified cellulose fibers used in the formulation examples are those represented by the following numbers 1 to 24. Such modified cellulose fibers can be produced by referring to the method of Production Example 1.

[0090] [Table 1]

[0091] Each modified cellulose fiber in Table 1 has an EO / PO copolymer portion as a modifying group, and the "modifying group" column in Table 1 lists the abbreviations of the compounds for providing each modifying group, as shown below. M2070: HUNTSMAN Jeffamine M2070 M2005: HUNTSMAN Jeffamine M2005 M1000: HUNTSMAN Jeffamine M1000

[0092] (2) Biomass-derived thermosetting compound (first agent) The biomass-derived thermosetting compounds used in the formulation examples are as follows:

[0093] [Table 2]

[0094] (3) Hardener (second and third parts) The following hardeners are used in the formulation examples.

[0095] [Table 3]

[0096] [Table 4]

[0097] The ratio of epoxy equivalent to active hydrogen in 4,4'-diaminodiphenyl sulfone (epoxy equivalent:active hydrogen) is 1:1, and the ratio of epoxy equivalent to acid anhydride equivalent in methylhexahydrophthalic anhydride (epoxy equivalent:acid anhydride equivalent) is 1:1.

[0098] (4) Inorganic fillers, etc. (fourth agent) The inorganic fillers used in the formulation examples are as follows. Here, a mixture of the components shown in Table 5 below is used as the fourth agent in the formulation examples.

[0099] [Table 5]

[0100] (5) Adhesives, structural material applications (fifth agent) The following organic particles are used as components for adhesive or structural material applications in the formulation examples. Here, a mixture of the components listed in Table 6 below is used as the fifth agent in the formulation examples.

[0101] [Table 6]

[0102] Next, formulation examples 1 to 21 are disclosed as formulation examples of resin compositions containing modified cellulose fiber / biomass-derived thermosetting compound / curing agent / inorganic filler, etc. Formulation examples 1 to 21 are base formulations, and by adding further components (for example, components for adhesive applications or components for structural materials) to the base formulation, agents for various applications (for example, paints, adhesives, insulating materials, structural materials) are prepared. Structural materials are applied to, for example, automobile, railway, and vehicle parts, ship parts, aviation-related parts, wind power generation propellers, housings for electrical parts, etc. For each formulation example, a specific formulation example having a composition described in combination numbers 1 to 24 is disclosed.

[0103] Formulation Example 1: Resin composition containing modified cellulose fiber / epoxidized soybean oil / 4,4'-diaminodiphenyl sulfone (DDS) / inorganic filler, etc. Formulation Example 1 discloses formulation examples of compositions described in the following combination numbers 1 to 24. The composition of combination number 1 is composed of the epoxidized soybean oil as the first agent in the amount (100 parts by mass) described in Table 2, the modified cellulose fiber of number 1 in the amount (2 parts by mass) described in Table 1, the DDS in the amount (40 parts by mass) described in Table 3, and the inorganic filler in the total amount (20.8 parts by mass) described in Table 5. The compositions described in the following combination numbers 2 to 24 are also composed of each component in the parts by mass and types described in each table, and the compositions of each combination number disclosed in the following formulation examples 2 to 21 are also similar.

[0104] [Table S-1]

[0105] Formulation Example 2: Resin composition containing modified cellulose fiber / epoxidized soybean oil / methylhexahydrophthalic anhydride (MHHPA) / 2-ethyl-4-methylimidazole (2E4MZ) / inorganic filler, etc. Formulation Example 2 discloses formulation examples having the compositions shown in the following combination numbers 1 to 24.

[0106] [Table S-2]

[0107] Formulation Example 3: Resin composition containing modified cellulose fiber / epoxidized soybean oil / dicyandiamide (DICY) / 3-(3,4-dichlorophenyl)-1,1-dimethylurea (DCMU) / inorganic filler, etc. Formulation Example 3 discloses formulation examples having the compositions shown in the following combination numbers 1 to 24.

[0108] [Table S-3]

[0109] Formulation Example 4: Resin composition containing modified cellulose fiber / epoxidized linseed oil / 4,4'-diaminodiphenyl sulfone (DDS) / inorganic filler, etc. Formulation Example 4 discloses formulation examples having the compositions shown in the following combination numbers 1 to 24.

[0110] [Table S-4]

[0111] Formulation Example 5: Resin composition containing modified cellulose fiber / epoxidized linseed oil / methylhexahydrophthalic anhydride (MHHPA) / 2-ethyl-4-methylimidazole (2E4MZ) / inorganic filler, etc. Formulation Example 5 discloses formulation examples having the compositions shown in the following combination numbers 1 to 24.

[0112] [Table S-5]

[0113] Formulation Example 6: Resin composition containing modified cellulose fiber / epoxidized linseed oil / dicyandiamide (DICY) / 3-(3,4-dichlorophenyl)-1,1-dimethylurea (DCMU) / inorganic filler, etc. Formulation Example 6 discloses formulation examples having the compositions shown in the following combination numbers 1 to 24.

[0114] [Table S-6]

[0115] Formulation Example 7: Resin composition containing modified cellulose fiber / epoxidized castor oil / 4,4'-diaminodiphenyl sulfone (DDS) / inorganic filler, etc. Formulation Example 7 discloses formulation examples having the compositions shown in the following combination numbers 1 to 24.

[0116] [Table S-7]

[0117] Formulation Example 8: Resin composition containing modified cellulose fiber / epoxidized castor oil / methylhexahydrophthalic anhydride (MHHPA) / 2-ethyl-4-methylimidazole (2E4MZ) / inorganic filler, etc. Formulation Example 8 discloses formulation examples having the compositions shown in the following combination numbers 1 to 24.

[0118] [Table S-8]

[0119] Formulation Example 9: Resin composition containing modified cellulose fiber / epoxidized castor oil / dicyandiamide (DICY) / 3-(3,4-dichlorophenyl)-1,1-dimethylurea (DCMU) / inorganic filler, etc. Formulation Example 9 discloses formulation examples having the compositions shown in the following combination numbers 1 to 24.

[0120] [Table S-9]

[0121] Formulation Example 10: Resin composition containing modified cellulose fiber / diglycidyl ether of isosorbide / 4,4'-diaminodiphenyl sulfone (DDS) / inorganic filler, etc. Formulation Example 10 discloses formulation examples having the compositions shown in Combination Numbers 1 to 24 below.

[0122] [Table S-10]

[0123] Formulation Example 11: Resin composition containing modified cellulose fiber / diglycidyl ether of isosorbide / methylhexahydrophthalic anhydride (MHHPA) / 2-ethyl-4-methylimidazole (2E4MZ) / inorganic filler, etc. Formulation Example 11 discloses formulation examples having the compositions shown in the following combination numbers 1 to 24.

[0124] [Table S-11]

[0125] Formulation Example 12: Resin composition containing modified cellulose fiber / diglycidyl ether of isosorbide / dicyandiamide (DICY) / 3-(3,4-dichlorophenyl)-1,1-dimethylurea (DCMU) / inorganic filler, etc. Formulation Example 12 discloses formulation examples having the compositions shown in Combination Numbers 1 to 24 below.

[0126] [Table S-12]

[0127] Formulation Example 13: Resin composition containing modified cellulose fiber / epoxidized cardanol / 4,4'-diaminodiphenyl sulfone (DDS) / inorganic filler, etc. Formulation Example 13 discloses formulation examples having the compositions shown in Combination Numbers 1 to 24 below.

[0128] [Table S-13]

[0129] Formulation Example 14: Resin composition containing modified cellulose fiber / epoxidized cardanol / methylhexahydrophthalic anhydride (MHHPA) / 2-ethyl-4-methylimidazole (2E4MZ) / inorganic filler, etc. Formulation Example 14 discloses formulation examples having the compositions shown in the following combination numbers 1 to 24.

[0130] [Table S-14]

[0131] Formulation Example 15: Resin composition containing modified cellulose fiber / epoxidized cardanol / dicyandiamide (DICY) / 3-(3,4-dichlorophenyl)-1,1-dimethylurea (DCMU) / inorganic filler, etc. Formulation Example 15 discloses formulation examples having the compositions shown in Combination Numbers 1 to 24 below.

[0132] [Table S-15]

[0133] Formulation Example 16: Resin composition containing modified cellulose fiber / epoxidized furan compound / 4,4'-diaminodiphenyl sulfone (DDS) / inorganic filler, etc. Formulation Example 16 discloses formulation examples having the compositions shown in Combination Numbers 1 to 24 below.

[0134] [Table S-16]

[0135] Formulation Example 17: Resin composition containing modified cellulose fiber / epoxidized furan compound / methylhexahydrophthalic anhydride (MHHPA) / 2-ethyl-4-methylimidazole (2E4MZ) / inorganic filler, etc. Formulation Example 17 discloses formulation examples having the compositions shown in Combination Numbers 1 to 24 below.

[0136] [Table S-17]

[0137] Formulation Example 18: Resin composition containing modified cellulose fiber / epoxidized furan compound / dicyandiamide (DICY) / 3-(3,4-dichlorophenyl)-1,1-dimethylurea (DCMU) / inorganic filler, etc. Formulation Example 18 discloses formulation examples having the compositions shown in Combination Numbers 1 to 24 below.

[0138] [Table S-18]

[0139] Formulation Example 19: Resin composition containing modified cellulose fiber / lignin-derived epoxy / 4,4'-diaminodiphenyl sulfone (DDS) / inorganic filler, etc. Formulation Example 19 discloses formulation examples having the compositions shown in Combination Numbers 1 to 24 below.

[0140] [Table S-19]

[0141] Formulation Example 20: Resin composition containing modified cellulose fiber / lignin-derived epoxy / methylhexahydrophthalic anhydride (MHHPA) / 2-ethyl-4-methylimidazole (2E4MZ) / inorganic filler, etc. Formulation Example 20 discloses formulation examples having the compositions shown in Combination Numbers 1 to 24 below.

[0142] [Table S-20]

[0143] Formulation Example 21: Resin composition containing modified cellulose fiber / lignin-derived epoxy / dicyandiamide (DICY) / 3-(3,4-dichlorophenyl)-1,1-dimethylurea (DCMU) / inorganic filler, etc. Formulation Example 21 discloses formulation examples having the compositions shown in Combination Numbers 1 to 24 below.

[0144] [Table S-21]

[0145] Next, formulation examples 22 to 27 are disclosed as formulation examples of adhesives and structural materials containing modified cellulose fiber / biomass-derived thermosetting compound / curing agent / inorganic filler etc. / organic particles. The structural materials are applied to, for example, automobile / railroad / vehicle parts, ship parts, aviation-related parts, wind power generation propellers, housings for electrical parts, etc. For each formulation example, a specific formulation example having a composition described in combination numbers 1 to 24 is disclosed.

[0146] Formulation example 22: Modified cellulose fiber / epoxidized soybean oil / dicyandiamide (DICY) / 3-(3,4-dichlorophenyl)-1,1-dimethylurea (DCMU) / inorganic fillers, etc. / adhesive containing organic particles Formulation Example 22 discloses formulation examples of compositions described in the following combination numbers 1 to 24. The composition of combination number 1 is composed of the amount (100 parts by mass) of epoxidized soybean oil as the first agent described in Table 2, the amount (2 parts by mass) of modified cellulose fiber No. 1 described in Table 1, the amount (5 parts by mass) of DICY described in Table 3, the amount (3 parts by mass) of DCMU described in Table 4, the total amount (20.8 parts by mass) of inorganic fillers, etc. described in Table 5, and the total amount (5 parts by mass) of organic particles described in Table 6. The compositions described in the following combination numbers 2 to 24 are similarly composed of each component in the parts by mass and types described in each table, and the compositions of each combination number disclosed in the following formulation examples 23 to 27 are also similar.

[0147] [Table S-22]

[0148] Formulation example 23: Adhesive containing modified cellulose fiber / epoxidized cardanol / dicyandiamide (DICY) / 3-(3,4-dichlorophenyl)-1,1-dimethylurea (DCMU) / inorganic fillers, etc. / organic particles Formulation Example 23 discloses formulation examples having the compositions shown in Combination Numbers 1 to 24 below.

[0149] [Table S-23]

[0150] Formulation Example 24: Structural material containing modified cellulose fiber / epoxidized soybean oil / methylhexahydrophthalic anhydride (MHHPA) / 2-ethyl-4-methylimidazole (2E4MZ) / inorganic fillers, etc. / organic particles Formulation Example 24 discloses formulation examples having the compositions shown in Combination Numbers 1 to 24 below.

[0151] [Table S-24]

[0152] Formulation Example 25: Structural material containing modified cellulose fiber / epoxidized linseed oil / methylhexahydrophthalic anhydride (MHHPA) / 2-ethyl-4-methylimidazole (2E4MZ) / inorganic fillers, etc. / organic particles Formulation Example 25 discloses formulation examples having the compositions shown in Combination Numbers 1 to 24 below.

[0153] [Table S-25]

[0154] Formulation Example 26: Structural material containing modified cellulose fiber / epoxidized cardanol / methylhexahydrophthalic anhydride (MHHPA) / 2-ethyl-4-methylimidazole (2E4MZ) / inorganic fillers, etc. / organic particles Formulation Example 26 discloses formulation examples having the compositions shown in Combination Numbers 1 to 24 below.

[0155] [Table S-26]

[0156] Formulation Example 27: Structural material containing modified cellulose fiber / lignin-derived epoxy / methylhexahydrophthalic anhydride (MHHPA) / 2-ethyl-4-methylimidazole (2E4MZ) / inorganic fillers, etc. / organic particles Formulation Example 27 discloses formulation examples having the compositions shown in Combination Numbers 1 to 24 below.

[0157] [Table S-27]

[0158] The above examples and formulations are illustrative of the embodiments of the present invention, and the present invention is not limited to these examples and formulations. [Industrial Applicability]

[0159] The resin composition of the present invention can be suitably used as a coating material, a molded body, an adhesive, or an insulating material in the fields of home appliance parts, electronics, aerospace, civil engineering and construction, ships, automobiles, wind power generators, drones, in-vehicle applications, passive components, electromagnetic wave materials, and the like.

Claims

1. A resin composition comprising modified cellulose fibers, a biomass-derived thermosetting compound, and a curing agent.

2. 2. The resin composition according to claim 1, wherein the modified cellulose fiber is an anionically modified cellulose fiber having a modifying group bonded to an anionic group of the anionically modified cellulose fiber.

3. The resin composition according to claim 1 or 2, further comprising at least one selected from the group consisting of an inorganic filler, a solvent and a dispersant.

4. A coating material comprising the resin composition according to any one of claims 1 to 3.

5. An adhesive comprising the resin composition according to any one of claims 1 to 3.

6. An insulating material comprising the resin composition according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Epoxy resin composition and insulative molding

    JP2016166350A